We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
56
1
avatar+404 

Let f(x)=x+3 and g(x)=3x+5. Find f(g(4))-g(f(4)).

 May 20, 2019

Best Answer 

 #1
avatar+18336 
+2

f(4) = 4+3 = 7

g(4) = 12+5 = 17        g (f(4)) = 21+5 = 26

 

 

f (g(4) - g(f(4))   will then equal     f( 17 - 26) = f(-9) = -9+3 = -6

 May 20, 2019
 #1
avatar+18336 
+2
Best Answer

f(4) = 4+3 = 7

g(4) = 12+5 = 17        g (f(4)) = 21+5 = 26

 

 

f (g(4) - g(f(4))   will then equal     f( 17 - 26) = f(-9) = -9+3 = -6

ElectricPavlov May 20, 2019

11 Online Users

avatar
avatar
avatar